Acceptability, feasibility, and cost of telemedicine for nonacute headaches: A randomized study comparing video and traditional consultations - Müller, Kai Ivar; Alstadhaug, Karl Bjørnar; Bekkelund, Svein Ivar (Journal of Medical Internet Research, 2016)
Source: doi:10.2196/jmir.5221 Backgr ound: The feasibility of telemedicine in diagnosing and treating nonacute headaches, such as primary headaches (migraine and tension-type) and medication-overuse headaches has not been previously investigated. By eliminating the need of travel to specialists, telemedicine may of fer significant time and money savings. Objectives: Our objective was to estimate the acceptance of telemedicine and investigate the feasibility and cost savings of telemedicine consultations in diagnosing and treating nonacute headaches. Methods: From September 2012 to March 2015, nonacute headache patients from Northern Norway who were referred to neurologists through an electronic application system were consecutively screened and randomized to participate in either telemedicine or traditional specialist visits. All patients were consulted by two neurologists at the neurological department in T romsø University Hospital. Feasibility outcomes were compared between telemedicine and traditional groups. Baseline characteristics and costs were then compared between rural and urban patients. T ravel costs were calculated by using the probabilistic method of the Norwegian traveling agency: the cheapest means of public transport for each study participant. Loss of pay was calculated based on the Norwegian full-time employee’ s average salary: < 3.5 hours=a half day’ s salary , > 3.5 hours spent on travel and consultation=one day’ s salary . Distance and time spent on travel were estimated by using Google Maps. Results: Of 557 headache patients screened, 479 were found eligible and 402 accepted telemedicine participation (83.9%, 402/479) and were included in the final analyses. Of these, 202 received traditional specialist consultations and 200 received telemedicine. All patients in the telemedicine group were satisfied with the video quality , and 198 (99%, 198/200) were satisfied with the sound quality . The baseline characteristics as well as headache diagnostics and follow-up appointments, and ...